Market Survey and Consumer Acceptance Studies of Ready-To-Eat Chicken Pepes Sausage in Malaysia - Mohamad Zulkepli, Nur Nabila Najwa; Muhammad, Norhayati (Enhanced Knowledge in Sciences and Technology, 2025)
The demand for the convenience of traditional food in ready-to-eat products is increasing, especially in today’s busy modern lifestyle. However, ready-to-eat products that do not meet the needs and demands of consumers will fail in the market. This study explores the market potential and consumer acceptance of ready-to-eat chicken pepes sausage, combining the traditional appeal of pepes with the practicality of modern food products. The primary aim was to evaluate market potential, assess consumer acceptance and identify essential recipe components for this innovative product. The methodology involved a competitive analysis using observation techniques conducted in physical stores and online markets, a structured questionnaire distributed to 385 respondents across Malaysia and a recipe survey using semi-structured interviews and secondary research to identify key ingredients and preparation methods. The competitive analysis and recipe survey were analyze using thematic analysis while, questionnaire was analyze using SPSS. Results revealed that are no similar products currently available, making it highly potential marketable with high interest among young adults aged 18-24 (34.81%) and adults aged 25-60 (32.99%). Key consumer preferences included a spicy flavor profile (60.8%), ease of preparation (35.6%), high protein (93.8%) and bite-sized version (52.2%). The recipe survey is identified essential ingredients such as chicken breast, coconut milk, lemongrass and traditional spices as critical for product development. This study concludes that the ready-to-eat chicken pepes sausage has strong potential for commercialization in the Malaysian market.